The effects of 5E learning strategies by image-based augmented reality of mobile learning for elementary students. (2015) - Chiang, Tosti H.C.; Yang, Stephen J.H.; Huang, Chester S.J.; Su, Addison Y.S.
The 5E teaching model which was based on a constructivism approach is used in the education field. It can be used in classrooms and can also effectively improve learning motivation. Besides, there are safety concerns when a teacher takes a whole class to a nearby water area to observe ecological activities. This study will be discussed the effects of combining 5E learning strategies with image-based augmented reality in the aquatic animal curriculum. A total of 53 fourth grade students in northern Taiwan participated in the experiment. Learning motivation and satisfaction levels of the experimental group students who used AR APP in learning about aquatic organisms was significantly higher than the control group students. The use of the AR APP with the 5E strategy teaching model has stimulated more students' interest in the topic, helping students discover new problems, and allowing students to think and observe things in a new way.